Implementasi Pembelajaran di Sekolah Ra Ar-Ridha - Khadijah Khadijah; Lailan Safira; Nadilla Barus; Nur Hidayatun; Risma Chintya (Peneliti.net, 2023)
The first six years of a child's life are called the golden period. At this time children are very concerned with growth and development in terms of intellectual, spiritual, physical, motor, emotional and social processes. This growth and development can be supported by the provision of educational stimuli. With early childhood education, they are able to learn in a fun way by applying the essence of play in their learning because play activities are the world of preschoolers. One of the learning models applied to teach early childhood is to use a center approach as is done in playgroups (KB). As for the several parts of the center which consists of four kinds of parts, namely the preparation center, the block center, the natural liquid center, and the creativity center. Teachers can help children to develop various aspects of their development and intelligence by implementing the center section. Sentra is the best integrated learning. This approach has proven to be very effective in early childhood learning